KETERKAITAN STRES KERJA DAN EMPLOYEE ENGAGEMENT DENGAN KEPUTUSAN RETENSI KARYAWAN - Yanthi, Ni Putu Dera; Cahyadi, Nyoman Dewi Pitaloka (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.06.TAHUN.2025, 2025)
Employee retention is one of the most significant challenges companies face across various industrial sectors. Work stress and employee engagement influence an employee's decision to stay or resign. This study examines the effects of work stress and employee engagement on retention decisions. By employing binary logistic regression analysis, the research seeks to understand the relationships between these variables and provide insights into managing work stress and enhancing employee engagement to strengthen employee retention. The study reveals that work stress has a significant impact on retention decisions. Indicators of work stress, such as excessive workload, role conflict, role ambiguity, time pressure, and job satisfaction, play a crucial role in increasing employee stress levels, ultimately leading to a higher intention to resign. On the other hand, employee engagement, which includes vigor, dedication, and absorption, positively influences retention decisions. Managing stress is key to addressing this issue. Implementing stress management strategies is hoped to help companies reduce work stress levels and improve employee well being.